2022
DOI: 10.1101/2022.07.20.500828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Misaligned chromosomes that satisfy the spindle assembly checkpoint are a strong predictor of micronuclei formation in dividing cancer cells

Abstract: SummaryChromosome alignment to the spindle equator is a hallmark of mitosis that is thought to promote chromosome segregation fidelity in metazoans. Yet, chromosome alignment is only indirectly supervised by the spindle assembly checkpoint (SAC) as a byproduct of chromosome bi-orientation, and the consequences of defective chromosome alignment remain unclear. Here we investigated how human cells respond to chromosome alignment defects of distinct molecular nature by following the fate of live HeLa cells after … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Because most anaphase lagging chromosomes in normal and cancer cells rarely form micronuclei and were recently shown to be actively corrected by an anaphase surveillance mechanism involving Aurora B activity at the spindle midzone (Orr et al, 2021; Sen et al, 2021), the presence of misaligned chromosomes that eventually satisfy the SAC upon long-term DNA damage might represent a higher risk for micronuclei formation and consequent genomic instability due to chromothripsis. Indeed, we recently found that systematic perturbation of kinetochore-microtubule attachments caused human cancer cells to enter anaphase after a delay with chronically misaligned chromosomes that eventually satisfy the SAC and missegregate, leading to the formation of micronuclei (Gomes et al, 2022). Thus, chronically misaligned chromosomes may represent a previously overlooked mechanism driving chromosomal/genomic instability during cancer cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Because most anaphase lagging chromosomes in normal and cancer cells rarely form micronuclei and were recently shown to be actively corrected by an anaphase surveillance mechanism involving Aurora B activity at the spindle midzone (Orr et al, 2021; Sen et al, 2021), the presence of misaligned chromosomes that eventually satisfy the SAC upon long-term DNA damage might represent a higher risk for micronuclei formation and consequent genomic instability due to chromothripsis. Indeed, we recently found that systematic perturbation of kinetochore-microtubule attachments caused human cancer cells to enter anaphase after a delay with chronically misaligned chromosomes that eventually satisfy the SAC and missegregate, leading to the formation of micronuclei (Gomes et al, 2022). Thus, chronically misaligned chromosomes may represent a previously overlooked mechanism driving chromosomal/genomic instability during cancer cell division.…”
Section: Discussionmentioning
confidence: 99%